Is the German apprenticeship system a panacea for the US labour market? - Dietmar Harhoff; Thomas J. Kane (Zentrum für Europäische Wirtschaftsforschung (ZEW); ZBW – Leibniz Information Centre for Economics, 1995)
Advocates of apprenticeship programs often argue as if it is simply a matter of historical accident which has hindered such investment by U.S. firms. This paper explores the structure of incentives undergirding the German system of apprenticeship training. First, we describe three characteristics of the German labor market which may lead firms to accept part of the cost of general training, even in the face of worker turnover. In the second part of the paper, we compare labor market outcomes for apprentices in Germany and high school graduates in the United States. Apprentices in Germany occupy a similar station within the German wage structure as held by high school graduates in the V.S. labor market. Finally, we provide evidence that the problem of forming labor market bonds is particularly acute for minority youth - in Germany as well as in the U.S.. We discuss some implications for the vocational training debate in the U.S.
Keywords: 330